The Impact of Weekday-to-Weekend Sleep Differences on Health Outcomes among Adolescent Students - Jinseok Kim; Jin-Won Noh; Ahraemi Kim; Young Dae Kwon (MDPI AG, 2022)
The sleep difference between weekdays and weekends can lead to negative physical and mental health outcomes in adolescents. Thus, this study has attempted to analyze the impact of sleep time differences on various health outcomes, using nationally representative panel data. Data from the junior high school student panel of the Korean Children and Youth Panel Survey were analyzed. The sleep difference was defined as the difference between the average sleep duration on weekdays and that on weekends in minutes. A series of mixed effect linear regression models for continuous variables or mixed effect logit regression for binary variables was utilized. Korean adolescent students reported from 96.8 min to 133.2 min of sleep duration difference between weekdays and weekends. After controlling for gender, parent work status, and type of housing, the weekday-to-weekend sleep differences were associated with various health-related outcomes including concentration difficulty, aggression, somatic symptoms, and withdrawal. Additionally, adolescent student life satisfaction was associated with sleep difference. The sleep differences among adolescent students were more associated with mental health-related outcomes and emotional symptoms than with physical health-related outcomes. The appropriate intervention to reduce the sleep difference gap is an important key to improve health in the adolescence period.